Development of Physical Qualities of Kurash Wrestling Girls - Parmonov Rustam Mizamovich (Genius Journals, 2022)
Our national struggle is developing widely in many countries of the world. At present, the development of new training methods in order for Uzbek wrestlers to raise the flag of our country at the world arenas is one of the important issues. Therefore, we have used special method of development of physical qualities of wrestlers and presented results in this article
Keywords: Physical attributes; physical preparation; technical preparation; special physical preparation